From embodied shame to reclaiming the stain: Reflections on a career in menstrual activism. Issue 4 (July 2019) - Quint, Chella
How did I come to embody and then ultimately reject the idea that periods, and period stains, are inherently dirty? How did I get from scrubbing period stains off my clothes at age 12 to crowdsurfing with a stain at a period demo in front of Parliament nearly 30 years later? Who influenced me and how have I influenced others to reject the idea that menstrual blood stains make us dirty? This article traces my 30-plus-year history of adventures in menstruating and my trajectory from embodying shame to thinking critically about how periods are presented to people of all genders – whether we menstruate or not – and trying to move the discourse through art and comedy, menstruating with pride and encouraging others to join me.